Acquisition of Program Graduate Traits of Teacher Interns in a Philippine State University: Implications for Elementary Teacher Education Management - Cabuquin, Jomar; Tolibas, Mae Caroline (Jurnal Pendidikan Indonesia, 2024)
This study aims to explore the correlation between program graduate trait acquisition (PGT) and the scholastic performance of elementary school teacher interns at a public university in Leyte, Philippines, and compare scholastic performance and PGT acquisition between male and female respondents. The research design was correlational and comparative, involving 40 respondents selected through purposive sampling. Data was collected using a 5-point Likert scale questionnaire to measure respondents' PGT and scholastic performance. Data analysis was performed using Spearman's rank correlation coefficient to examine the relationship between PGT and scholastic performance and the Mann-Whitney Wilcoxon Test to examine gender differences in PGT acquisition and scholastic performance. The results showed no significant correlation between PGT acquisition and scholastic performance. Additionally, there were no significant gender differences in PGT acquisition, highlighting the importance of recognizing individual skills without regard to gender stereotypes. However, the results showed that male respondents demonstrated superior scholastic performance to female respondents, suggesting that educational choices may be better suited to individual strengths. The implications of these findings can encourage the development of educational programs that are more inclusive and support the development of individual potential regardless of gender.